Once upon a time in the East a story of growing up - Guo, Xiaolu 1973- (Vintage, 2017)
Xiaolu Guo meets her parents for the first time when she is almost seven. They are strangers to her. When she is born her parents hand her over to a childless peasant couple in the mountains. Aged two, and suffering from malnutrition on a diet of yam leaves, they leave Xiaolu with her illiterate grandparents in a fishing village on the East China Sea. It's a strange beginning. Guo's extraordinary memoir is a handbook of life lessons. How to be an artist when censorship kills creativity and the only job you can get is writing bad telenovela scripts. How to be a woman when female babies are regularly drowned at birth and sexual abuse is commonplace. Most poignantly of all: how to love when you've never been shown how.